Peran Kepercayaan Diri dan Dukungan Sosial Terhadap Krisis Seperempat Abad (Quarter Life Crisis) Pada Mahasiswa Semester Akhir - Wulandari, Putu Eka Wahyu; Suarya, L M Karisma Sukmayanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Humans will go through early adulthood between the ages of 18-29 years old. During this period, individuals may experience some instability or emotional crisis, also known as a quarter-life crisis. Self-confidence and social support is said to be the factor that influences an individual's ability to cope with the crisis. The objective of this study is to determine the role of self-confidence and social support in the quarter-life crisis among final year students. The sampling technique used in this study cluster sampling, in which the sample obtained is the Faculty of Medicine at Udayana University, with a total of 123 participants. Multiple regression analysis technique was used to analyze the data, the result showed an F value of 135.739 with a significance level of 0.000, and an R2 value of 0.693. These values indicate that self-confidence and social support play a role in quarter-life crisis by 69.3%. The results of this research are expected to provide information and input to assist final year students in facing the quarter-life crisis by enhancing self-confidence and seeking social support from their closest ones.